Effects of the Oral Health Promotion Program on oral health and oral microbiota changes in diabetic elderly individuals: a quasi-experimental study - Fan Liu; Siping Song; Shuqi Huang; Jing He; Xin Ye; Liwei Hu; Xin Zeng; Sicheng Deng; Xiuying Hu (BMC Oral Health)
Abstract Background Diabetes with its highly prevalence has become a major contributor to the burden of health care costs worldwide. Recent unequivocal evidence has revealed a bidirectional link between oral health and diabetes. In this study, the effects of the Oral Health Promotion Program (OHPP) on oral hygiene, oral health-related quality of life and glycated haemoglobin (HbA1c) levels in diabetic elderly were examined. Moreover, microbial changes in the saliva microbiota community were also emphatically investigated. Methods A quasi-experiment was conducted in regionally representative communities to assess oral health and oral microbiota of the elderly diabetic participants. The participants in the intervention group (n = 26) received OHPP including three phases of cognition, intensification and consolidation during the program, when those in the control group (n = 26) received routine oral care. Clinical parameters were recorded at two different time points as before the study (T0), and 3 months after intervention onset (T1). Oral health was measured via the oral health impact profile (OHIP-14) questionnaire, dental plaque index, HbA1c and mastery of oral health knowledge, and sequencing of the 16S rRNA gene from saliva samples was used to analyze the oral microbiota. Results The average age of the final sample was 71.77 years (SD = 6.06), 53.8% (28/52) of whom were male. A reduction in the plaque index and improvements in oral health-related quality of life and mastery of oral health knowledge were observed in the intervention group. Meanwhile, the α-diversity of the microbiota increased in both groups, but more significant in the intervention group. PCoA analyses showed significant differences in microbial community structure in both groups, and LEfSe analyses revealed a decrease of g_Streptococcus and g_Rothia after the implementation of OHPP and a decrease of g_Streptococcusa, g_Porphyromonas, g_Gemella after the routine oral care. There was no statistically significant difference in the HbA1c level between two groups. Conclusions OHPP superiorly contributes to the improvement of oral health and oral microbiota in elderly diabetic patients. The overarching goal is to introduce attention to the importance of good oral health as a crucial point in preventing and managing diabetes mellitus and thereby make it a meaningful contribution to public health and geriatric care. Trial registration This study was retrospectively registered in Chinese Clinical Trial on October 9, 2022 (ID ChiCTR2200064453).